Effect of Iron and Folic Acid Supplementation on the Infants Birth Weight: A Meta-Analysis - Atiqoh Khoirunnisa' Maftuch; Bhisma Murti; Setyo Sri Rahardjo; Ika Sumiyarsi Sukamto; Revi Gama Hatta Novika (Journal of Maternal and Child Health, 2025)
Background: Low birth weight (LBW), defined as a birth weight of less than 2,500 grams, is associated with an increased risk of neonatal mortality and developmental disorders. Efforts to prevent and manage LBW can be made through the administration of iron and folic acid supplements during pregnancy. This study aims to estimate and analyze the effect of iron and folic acid supplementation on the birth of infants with low birth weight. Subjects and Method: This study is a systematic review and meta-analysis of relevant previous studies conducted using the PRISMA guidelines. The population included pregnant women, interventions involving iron and folic acid supplementation compared to no supplementation, and outcomes related to low birth weight. Article searches were conducted in the PubMed, ScienceDirect, Scopus, and Google Scholar databases, published between 2013 and 2025. The search terms were ("Pregnant woman" OR "Expectant mother") AND ("Iron and folic acid supplements" OR "IFA supplements") AND ("Low Birth Weight" OR "Low-weight newborns"). Inclusion criteria included full-text articles with a cross-sectional study design and reporting adjusted odds ratio (aOR) values. Findings from the primary research articles were analyzed using Review Manager 5.3. Results: The included primary studies comprised 21 articles from China, India, Nepal, Pakistan, Malawi, and Ethiopia. The results of this meta-analysis indicate that pregnant women who consumed iron and folic acid supplements had an average 0.87 unit lower risk of giving birth to LBW infants compared to pregnant women who did not consume iron and folic acid supplements (aOR= 0.87; 95% CI = 0.75 to 1.00; p= 0.040). Conclusion: The administration of iron and folic acid supplements can reduce the incidence of low birth weight.